Challenges Associated with Informed Consent in Low- and Low-Middle-Income Countries - Upjohn, Melissa; Wells, Kimberly (Frontiers in Veterinary Science, 2016)
Frontiers in Veterinary Medicine endorse the Helsinki declaration and guidelines of the International Committee of Medical and Journal Editors, including the requirement to obtain informed consent from all research participants. Whilst the concept of informed consent is well understood in western research environments, its components require further consideration when reviewing studies involving humans and owned animals in low- and middle-income countries (LMICs) in order to take account of different social, educational and research norms. This piece identifies some of the challenges that need to be considered and how they might affect the process of obtaining informed consent. It explains the approach taken by an animal welfare non-governmental organization working in LMICs to addressing these challenges. It also identifies questions that reviewers might consider when asked to comment on work originating in this context.